GW24-e3549 Role of heart-type fatty acid-binding protein in assessing prognosis of acute pulmonary embolism. (1st October 2013) - Li,; Li, Bingong
Abstract : Objectives: To study the role of heart-type fatty acid-binding protein (H-FABP) in assessing prognosis of acute pulmonary embolism (APE). Methods: The levels of plasmid H-FABP and cTnI and D-Dimer in 72 patients with APE and 30 healthy controls were determined. The associations between the biomarkers and the severe complications were determined though a logistic regression model. Results: The levels of D-Dimer in patients with APE were significantly higher than that in healthy controls (P < 0.01). The incidence of severe complications in the H-FABP-positive group of APE was higher than in the H-FABP negative group (66.7% vs 3.5%, P < 0.05). By logistic regression, elevated H-FABP was associated with a 50.44-fold increase in the death or complication risk (95%CI: 7.40-342.88, P < 0.001). Conclusions: The H-FABP might be a useful biomarker for prediction prognosis of patients with APE.